1996
DOI: 10.1111/j.1365-2583.1996.tb00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the Anopheles gambiae 2L telomeric region via an integrated transgene

Abstract: A Drosophila P-element derivative (pUChsneo) integrated into the telomeric region of the left arm of the second chromosome of Anopheles gambiae was used to clone the proximally flanking An. gambiae sequences. Molecular analyses revealed that the pUChsneo construct was partially duplicated and had integrated into a subterminal minisatellite. This satellite has a repeat unit of 820 bp and is located exclusively at the tip of 2L. No sequence similarity to subterminal minisatellites from other dipterans was detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 48 publications
0
66
1
Order By: Relevance
“…The simplest model to explain the observations that the 2L chromosome extensions are composed of sequences already present near the end of the chromosome and do not contain any new sequences typical of telomerase elongation or transpositions is that the chromosomes elongate by an unequal crossing over mechanism. The early mapping of the pUChsneo transgene in the G418 A. gambiae stock (11) together with recent detailed studies (3) indicated that a complete and a partial copy of the transgene were integrated at or near the end of the chromosome. We propose that this chance integration allowed elongation of the chromosome by terminal gene conversion as shown diagrammatically in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The simplest model to explain the observations that the 2L chromosome extensions are composed of sequences already present near the end of the chromosome and do not contain any new sequences typical of telomerase elongation or transpositions is that the chromosomes elongate by an unequal crossing over mechanism. The early mapping of the pUChsneo transgene in the G418 A. gambiae stock (11) together with recent detailed studies (3) indicated that a complete and a partial copy of the transgene were integrated at or near the end of the chromosome. We propose that this chance integration allowed elongation of the chromosome by terminal gene conversion as shown diagrammatically in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Due to size heterogeneity, the terminal DNA fragments from a pool of approximately 50 mosquitoes appeared as a broad band characteristic of chromosome termini (3). In order to assess the extent of size polymorphism at the telomere, DNA from individual mosquitoes was assayed.…”
Section: L Chromosome Ends In 1993mentioning
confidence: 99%
See 1 more Smart Citation
“…Recombination between these complex repeat sequences has been proposed as a mechanism for chromosome length maintenance in these species. It should be noted that 'lower' dipterans, such as the midge Chironomus and the mosquito Anopheles, which may resemble a Drosophila ancestor, fall into this category (55,98,99).…”
Section: Evolution Of Drosophila Telomeresmentioning
confidence: 99%
“…The ends of chromosomes in the fruit fly Drosophila melanogaster are maintained by occasional transposition of retrotransposons (4,24,53). Other organisms, including the midge Chironomus sp., the mosquito Anopheles gambiae, and the plant Alium cepa, have telomeres composed of complex repeat families that are thought to be maintained by recombination (5,13,43,47).…”
mentioning
confidence: 99%